Mechanisms and age estimates of continental-scale endorheic to exorheic drainage transition: Douro River, Western Iberia - Cunha, Pedro (2020)
In western Iberia, mechanisms that can explain the transition from endorheic to exorheic continental-scale drainage reorganization are foreland basin overspill, headwards erosion and capture by an Atlantic river, or a combination of both. To explore these, we have investigated the Portuguese sector of the Douro River, the locus of drainage reorganization. The Douro River is routed downstream through the weak sedimentary infill of the Douro Cenozoic Basin, after which the river cuts down through harder granitic and metamorphic rocks crossed by active fault zones, before reaching the Atlantic coast. We investigated the drainage reorganization using an integrated approach that combined remote sensing, field survey and geochronology, applied to Pliocene–Quaternary fluvial sediments and landforms. The older drainage record is documented by a series of high and intermediate landform levels comprising: (1) a high level (1000–500 m a.s.l.) faulted regional fluvial erosion surface, the North Iberian Meseta planation surface and the Mountains and Plateaus of Northern Portugal, recording the endorheic drainage of the Douro Cenozoic Basin; (2) a first inset level at 650–600 m a.s.l., comprising a broad fluvial surface developed onto a large ENE–WSW depression, interpreted as recording the initiation of the continental scale reorganization; and (3) an inset fluvial surface at 550–400 m a.s.l., corresponding to the establishment of the exorheic ancestral Douro valley. The younger drainage record comprises an entrenched fluvial strath terrace sequence of up to 9 levels (T9 = oldest), positioned at 246–242 m above the modern river base; T1 = youngest, positioned at +17–13 m. Levels T1 and T3 display localized fault offsets. The three lowest terrace levels (T3–T1) were dated using optically stimulated luminescence techniques with results ranging from >230–360 ka (T3), through 57 ka (T2) to 39–12 ka (T1). Fluvial incision rates of the younger terraces were quantified and temporally extrapolated to model the ages of the intermediate to high elevation levels of the early drainage record. Integration of incision data informs on the probable timing of the drainage reorganization and the initial adjustment, ~3.7–1.8 Ma. This was followed by acceleration of incision, producing the entrenched river terrace sequence developed via spatial and temporal variations in rock strength, uplift and cyclic cool-climate variability as the river adjusted to the Atlantic base level.